The Effect of Collaborative Strategic Reading on Students Biographical Writing Skills - Ade Iqlimah; Abdurrahman; Yulianti Rasyid; Delsy Alma Putri (Raja Zulkarnain Education Foundation, 2026)
Collaborative Strategic Reading (CSR) is a reading comprehension teaching strategy that combines cognitive strategies with small group cooperative learning to help students improve reading comprehension and vocabulary through four main strategies: preview, click and clunk, get the gist, and wrap up. This study aims to describe: 1) biographical text writing skills in learning without using CSR; 2) biographical text writing skills in learning using CSR; 3) the effect of CSR on biographical text writing skills. This study used a posttest only control group design. The study population was all students of class XE1 and XE2 of SMA Negeri 1 Tanjung Mutiara in the 2025/2026 academic year who participated in learning in both the control and treatment classes. They numbered 72 students. The research sample was determined to be 35 students from each population group. Data on biographical text writing skills were collected using a performance test that was compiled objectively and systematically. The results of the requirement test showed that the data on biographical text writing skills were not normally distributed. Therefore, the data of biographical text writing skills were analyzed using a one-sample chi-square nonparametric inferential statistical procedure instead of a one-sample t-test. The data of the influence of CSR on biographical text writing skills were analyzed using a nonparametric inferential statistic, namely the Mann-Whitney test. The results of the study: 1) the mean post-test of biographical text writing skills of the control class was sufficiently qualified; 2) the mean post-test of biographical text writing skills of the experimental class was well qualified; 3) CSR has an influence on learning biographical text writing skills.